Sergey Redkin performs Prokofiev's Piano sonata no. 9 - Prokofiev, Sergey 1891-1953 (Telmondis - Münchner Philharmoniker, 2017)
Bronze medalist at the 2015 International Tchaikovsky Competition, Sergey Redkin gives here a performance of Prokofiev's Piano Sonata No. 9 as part of the 2016 MPHIL 360°. For the 2016 festival, Valery Gergiev and the Münchner Philharmoniker put together a musical celebration of impressive proportions! The three-day festival put a special focus on Sergei Prokofiev's piano sonatas performed by honorees of the International Tchaikovsky competition.
Keywords: Sonatas (Piano); Internet videos